First measurement of the angular coefficients of Drell-Yan e(+)e(-) pairs in the Z mass region from pp¯ collisions at √s=1.96 TeV. - Aaltonen, T; González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2011)
We report on the first measurement of the angular distributions of final state electrons in pp¯ → γ*/Z → e(+)e(-) + X events produced in the Z boson mass region at √s1.96 TeV. The data sample collected by the CDF II detector for this result corresponds to 2.1  fb(-1) of integrated luminosity. The angular distributions are studied as a function of the transverse momentum of the electron-positron pair and show good agreement with the Lam-Tung relation, consistent with a spin-1 description of the gluon, and demonstrate that, at high values of the transverse momentum, Z bosons are produced via quark-antiquark annihilation and quark-gluon Compton processes.